Influence of new qualitative productivity forces on quality-effective change in China’s Yangtze river economic belt sports industry: The mediating effect of industry–University–Research Cooperation - Xiuqin Chen; Songzhong Ye (PLoS ONE, 2025)
Due to the lack of empirical research on the influence of new qualitative productivity forces on quality-effective change in the sports industry, entropy-weighted threshold-based estimation (TOPSIS) is used based on panel data for 11 provinces and cities in China’s Yangtze River Economic Belt from 2016–2022. The results are used to measure the levels of new qualitative productivity forces and quality-effective change in the sports industry and to analyze the relationships among these factors and industry–university–research cooperation through a bidirectional fixed effects model and a mediating effects model. The study reveals that new qualitative productivity forces have a significant positive effect on quality-effective change in the sports industry that is heterogeneous by region. Industry–university–research cooperation plays a partially intermediary role in promoting quality-effective change in the sports industry through new qualitative productivity forces. In this context, we propose the following measures: focus on cultivating new-quality industries and strengthening their application in the sports industry, emphasize the intermediary effect of industry–university–research cooperation to promote quality-effective change in the sports industry, formulate strategies according to local conditions, and focus on the development of new qualitative productivity forces in sports.